2018
DOI: 10.15406/ijfcm.2018.02.00100
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and management practices regarding dengue fever among doctors of tertiary care hospital

Abstract: Introduction: Worldwide incessantly menace "Dengue Fever" is a health phenomenon nowadays. We targeted three big provinces of Pakistan including Sindh, Punjab, and Khyber Pukhtoon Khwan. It makes a figure of 21,580 dengue cases and out of them, 317 patients fall in death group. Materials and methods: A cross-sectional case-control study has been conducted at the general tertiary care hospital in Karachi, Pakistan. Physicians, Residents and Interns from all the specialty of targeted the hospital, were included.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Another KAP study showed that only a moderate level of knowledge was observed in 49 percent of the HCPs, with room for improvement in their level of attitude and practice concerning dengue fever (dengue without warning sign) prevention [29]. One study reported that almost every physician in the sample knew that aspirin and non-steroidal anti-inflammatory drugs must be avoided during dengue fever or shock syndrome (severe dengue) [30]. However, other studies reported that physicians lacked knowledge about clinical signs, symptoms, and treatment for dengue patients [31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another KAP study showed that only a moderate level of knowledge was observed in 49 percent of the HCPs, with room for improvement in their level of attitude and practice concerning dengue fever (dengue without warning sign) prevention [29]. One study reported that almost every physician in the sample knew that aspirin and non-steroidal anti-inflammatory drugs must be avoided during dengue fever or shock syndrome (severe dengue) [30]. However, other studies reported that physicians lacked knowledge about clinical signs, symptoms, and treatment for dengue patients [31].…”
Section: Introductionmentioning
confidence: 99%
“…One published study anticipated there were significant variations in clinical practice by physician's age group and practice setting [27]. At the same time, other published studies reported that the KAP of healthcare professionals for dengue fever was not well established [29,30,32]. To our best knowledge, there were no KAP studies conducted among physicians in India, Bangladesh, Malaysia, and Turkey.…”
Section: Introductionmentioning
confidence: 99%